Delphi exploration of subjective well-being indicators for strategic urban planning towards sustainable development in Malaysia - Danladi, Musa Haruna; Yacob, Mohd Rusli; Abdullah, Ahmad Makmom (Elsevier, 2019)
This study expert consensus to determine indicators that could be used to assess subjective well-being for strategic urban planning in the context of sustainable development. For this purpose, a Delphi study including a panel of 45 academic experts was carried out. The study consisted of two rounds. At each round, experts were asked to rate key elements by assessing indicator as very low importance, low importance, moderate importance, high importance and very high importance. A75% agreement was used as cutoff. The results at second round reveal that panelists agreed on 37 key indicators being essential to assess subjective well-being for sustainable urban development.Using these results as a framework to develop guidelines at local,state, and national levels would allow better assessing and comparing transition programs to-wards sustainability.